Chapter The Role of Adult Learning and Education in (Post-)Covid Times - Popovic, Katarina (Studies on Adult Learning and Education, 2023)
The COVID-19 pandemic has caused unprecedented disruptions to global education systems, with adult education shifting to a virtual world and relying heavily on digital and ICT tools to maintain continuity of learning. However, the prolonged pandemic raises important questions about the future of adult education. The current essay examines the most significant changes in three key areas of adult education: health, citizenship, and digital technologies. It argues that adult education should not only equip people with the knowledge and skills necessary to navigate a crisis, but also play a proactive role in shaping the future of education and the world. It should critically analyse and challenge mainstream ideas and offer constructive alternatives to proposed solutions.